МEDIA AND CRIMINAL BEHAVIOR – BETWEEN SOCIAL RESPONSIBILITY AND DESTRUCTION - Željko Bjelajac; Aleksandar Filipović (Pravo, 2023)
This paper examines the interplay between media and criminal activities, highlighting the numerous stereotypes and misconceptions about criminality that often originate from the media’s construction of reality, driven by sensationalism and profit-seeking. In scrutinizing the media’s engagement with criminal matters, the paper comprehensively analyzes the intricate dynamic between providing informative content and the allure of sensationalism. The paper accentuates the pivotal role of the media in disseminating information to the public, promoting justice, and stimulating discourse on the causal factors and repercussions of criminal behavior. The paper underscores the adverse societal impacts of the media, including the propagation of disinformation, the endorsement of violence and aggression, the cultivation of media dependency, and the ramifications for mental health. It meticulously explores the dissemination of false news, identifies sources of disinformation, and formulates strategies to mitigate this predicament. The nexus between the media’s portrayal of violence and tangible instances of aggressive conduct is scrutinized, delving into industry self-regulation and the roles played by family, education, and society in addressing this issue. Furthermore, the paper conducts an in-depth analysis of how the media portrays criminal activities, with a particular emphasis on popular television genres centered on criminal themes. It elucidates the psychological dimension of the appeal of such narratives, offering insights into diverse motivators prompting viewers to identify with criminal acts. In conclusion, the paper presents an empirical research into the perceptions of citizens in Serbia concerning the influence exerted by both legacy and new media.